Local structure in deeply supercooled liquids exhibits growing lengthscales and dynamical correlations - James E. Hallett (Nature Portfolio, 2018)
The glass transition remains an unsolved problem due to the scarcity of particle-resolved data over a large dynamic range. Hallett et al. probe an unprecedented time window and show a strong correlation between local structure and slow dynamics in a deeply supercooled liquid of colloids.